In vitro cell signaling events of 2-methoxyestradiol-bis-sulphamate in a breast adenocarcinoma- and a non-tumorigenic breast epithelial cell line - Joubert, Annie M. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.